Molecular Characteristics of Shenfu Coal Characterized by Mass Spectrometers with Three Ion Sources. Issue 37 (2nd October 2018) - Fan, Xing; Yu, Guo; Zhao, Yun‐Peng; Wang, Rui‐Yu; Wei, Xian‐Yong; Ma, Feng‐Yun; Liu, Jing‐Mei; Zhang, Xiao‐Yun; Zhao, Wei
Abstract: A coal sample was extracted at 300 o C sequentially with cyclohexane, acetone and methanol to obtain three filtrates. Mass spectrometers coupled with various commercial ion sources such as electron ionization (EI), electrospray ionization (ESI) or atmospheric pressure photoionization (APPI) were used to acquire a full view of molecular information for the coal and build up the analytical strategy for aromatics. Phenols, furans and ketones were the most abundant products in the filtrates of cyclohexane, acetone and methanol, respectively, which were obtained by mass spectrometer with EI source. ESI well ionized compounds with high polarity and high molecular weight (900 Da), but not for aromatics with ring number over 2. APPI enhanced the ionization efficiency for compounds with both high molecular weight and high aromatic ring size, which is the best one for the analysis of aromatics. Abstract : The thermal dissolution products of a low‐rank coal were analyzed by mass spectrometry with various ion sources to acquire a full view of molecular information for the coal and build up the analytical strategy for aromatics. Phenols, furans and ketones were the most abundant products in the coal extracts according to the MS data from EI source. APPI enhanced the ionization efficiency for molecules in the coal with both high molecular weight and high aromatic ring size.